Environmental security and ecoterrorism - Alpas, Hami.; Berkowicz, Simon M.; Ermakova, Irina; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
In recent years, the concept of environmental security has been adapted to include preparedness for acts of ecoterrorism. This latter term has now become synonymous with environmental terrorism where the perpetrator uses the environment as a weapon to harm an opponent. The intended outcome is usually large-scale deaths, severe damage to the environment, and instilling fear in the general population. This book explores various facets of ecoterrorism including the role of the state in pursuing and maintaining environmental security, a review of the concept of ecoterrorism, food security challenges and weaknesses, technological countermeasures to enable rapid detection or response, and existing pollution sources and hazards that may serve as targets for terrorist acts. In sum, this volume provides a useful overview for both the layperson and experienced researchers.
Preface. Contributors. Food Chain Security Pilot Study: Findings and recommendations -- Food Chain Security and Vulnerability -- The Contribution of Food Safety Management Systems to the Prevention of Deliberate Food Contamination -- Issues of Food Chain Security and Case Studies in the Czech Army.-Food Chain Security in Romania.-New system of food control in Russia -- Food Chain Defense in the United States -- Food Safety Strategies in the Federal Republic of Germany -- Assessing security of supply three methods used in Finland.-Food chain defense and its potential implications on traditional foods. The Portuguese case -- Subject Index.
Electronic reproduction.
Keywords: Ecoterrorism -- Congresses; Environmental protection -- Congresses; Ecoterrorism; Electronic books